Three new Craticula species (Bacillariophyta) from the Maritime Antarctic Region - van De Vijver, Bart; Kopalova, Katerina; Zidarova, Ralitsa (Phytotaxa, 2015)
Three new diatom taxa belonging to the genus Craticula were found during the ongoing taxonomic revision of the Antarctic freshwater and limno-terrestrial diatom flora: Craticula australis, sp. nov., C. obaesa, sp. nov and C. petradeblockiana, sp. nov. Detailed light and scanning electron microscope observations are used to better characterize the morphology and ultrastructure of these three new taxa. A fourth Craticula taxon, formerly identified as Navicula megacuspidata, described from South Georgia, is transferred to the genus Craticula and its taxonomy is briefly discussed. Comparisons with similar taxa and the ecological preferences of each species are added. The revision of these species confirms once again the endemic nature of the Antarctic diatom flora.